2009
DOI: 10.1111/j.1365-313x.2009.03861.x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora1 phosphorylation activity on histone H3 and its cross‐talk with other post‐translational histone modifications in Arabidopsis

Abstract: SUMMARYThe enzymological properties of AtAurora1, a kinase responsible for the cell cycle-dependent phosphorylation of histone H3 at S10, and its cross-talk with other post-translational histone modifications, were determined. In vitro phosphorylation of H3S10 by AtAurora1 is strongly increased by K9 acetylation, and decreased by K14 acetylation and T11 phosphorylation. However, S10 phosphorylation activity is unaltered by mono-, di-or trimethylation of K9. An interference of H3K9 dimethylation by SUVR4 occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 89 publications
2
54
0
Order By: Relevance
“…4, E and F). Our results were consistent with previous in vitro biochemical studies, which showed that Aurora B does not have substrate preference for a trimethylated form of H3K9 peptide, among other modified forms of the same peptide (35)(36)(37).…”
Section: H3k9 Was Not Required For Asymmetric Distribution Of the Neisupporting
confidence: 83%
See 2 more Smart Citations
“…4, E and F). Our results were consistent with previous in vitro biochemical studies, which showed that Aurora B does not have substrate preference for a trimethylated form of H3K9 peptide, among other modified forms of the same peptide (35)(36)(37).…”
Section: H3k9 Was Not Required For Asymmetric Distribution Of the Neisupporting
confidence: 83%
“…Peptide sequences that were not analyzed in this study are in gray. The H3.1/2(27-40) peptide is in blue, and the H3.3 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) peptide is in red. The line connecting the four acetylation marks on H4(2-16) peptide indicates only the four-ac was enriched on old H4 but not two-ac or three-ac (Table 1).…”
Section: Mass Spectrometry Provides a Powerful Tool To Study Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of this group of genes after completion of the cell division and expansion stages of leaf development is to be expected, but the increase in expression at the end of senescence is unanticipated. AURORA1 has been shown to phosphorylate histone H3 at Ser10 (Demidov et al, 2009), and, in mammalian cells, this modification has been suggested to have a crucial role in transcription and apoptosis as well as in cell division (Prigent and Dimitrov, 2003). These proteins may alter chromatin structure in late senescence to allow DNA fragmentation and eventual degradation.…”
Section: Upregulated Gene Clusters Illustrate the Complexity Of The Smentioning
confidence: 99%
“…This group is highly enriched for genes involved in the cytoskeleton (see Supplemental Figure 3B online), with members of the a-tubulin family (TUA2, 4, and 5), actin genes, ACT3 and ACT11, and two aurora genes (AURORA1 and AURORA2) encoding kinase proteins that have a role in histone phosphorylation and have been reported to be associated with microtubule spindles and abundantly transcribed only in dividing cells (Demidov et al, 2005(Demidov et al, , 2009). Downregulation of this group of genes after completion of the cell division and expansion stages of leaf development is to be expected, but the increase in expression at the end of senescence is unanticipated.…”
Section: Upregulated Gene Clusters Illustrate the Complexity Of The Smentioning
confidence: 99%